2021
DOI: 10.3390/jcm10050935
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Carotid Revascularization in Retrospective Case Series

Abstract: Background: Most data in carotid stenosis treatment arise from randomized control trials (RCTs) and cohort studies. The aim of this meta-analysis was to compare 30-day outcomes in real-world practice from centers providing both modalities. Methods: A data search of the English literature was conducted, using PubMed, EMBASE and CENTRAL databases, until December 2019, using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement (PRISMA) guidelines. Only studies reporting on 30-day outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the present study, the incidence of composite complications (death, stroke, or MI) during the first 30 days after the CAS was 2.6%. This rate was 4.4% (symptomatic and asymptomatic), 9.6% (symptomatic), 7.7% (symptomatic), 5.1% (symptomatic and asymptomatic), 8.5% (symptomatic, at 120 days), and 4.23% (symptomatic and asymptomatic) in CAS arm of SAPPHIRE, 23 EVA‐3S, 24 SPACE, 25 CREST, 26 ICSS 12 trials, and a metanalysis of 15 retrospective case series, 27 respectively. The 30‐day complication rates in the current study were lower than observed in previous studies but comparable to more recent studies 28,29 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present study, the incidence of composite complications (death, stroke, or MI) during the first 30 days after the CAS was 2.6%. This rate was 4.4% (symptomatic and asymptomatic), 9.6% (symptomatic), 7.7% (symptomatic), 5.1% (symptomatic and asymptomatic), 8.5% (symptomatic, at 120 days), and 4.23% (symptomatic and asymptomatic) in CAS arm of SAPPHIRE, 23 EVA‐3S, 24 SPACE, 25 CREST, 26 ICSS 12 trials, and a metanalysis of 15 retrospective case series, 27 respectively. The 30‐day complication rates in the current study were lower than observed in previous studies but comparable to more recent studies 28,29 .…”
Section: Discussionmentioning
confidence: 95%
“…(symptomatic, at 120 days), and 4.23% (symptomatic and asymptomatic) in CAS arm of SAPPHIRE, 23 EVA-3S, 24 SPACE, 25 CREST, 26 ICSS 12 trials, and a metanalysis of 15 retrospective case series, 27 respectively. The 30-day complication rates in the current study were lower than observed in previous studies but comparable to more recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in asymptomatic low-risk surgical patients with severe carotid stenosis, comparison of stroke, death, and myocardial infarction rates within 30 days, at 1and 5-years following CAS with emboli protection device or CEA revealed nonsignificant differences (11). A recent meta-analysis of real-world practices of both CAS and SEA concluded non-significant differences of the 30-day neurologic events (CEA: 2.1% and CAS: 2.6%) (12).…”
Section: Discussionmentioning
confidence: 98%